Smartphone Purchase Intention by Nilai University Students Living in the City of Nilai Malaysia - Lee En En; Balakrishnan Balakrishnan (Faculty of Economics, Universitas Sriwijaya, 2022)
Smartphone purchases during the Covid-19 pandemic increased for a niche purpose, online learning. The demand was critical for retailers to understand niche market’s needs, wants, and preferences. Previous study shows that research was mainly focused on main cities. The study aims to investigate smartphone purchase intention from a small-niche market’s perspective. Literature on purchase intentions was explored to review the purchase influence factors. A survey was conducted on Nilai University students living in Nilai about 50 kilometres from the city centre through an online survey method due to movement order control restrictions. A total of 184 sets of questionnaires were collected. The convenience sampling method was adopted to analyse the data in the SPSS software. The results show a positive relationship between the influence factors and purchase intention. The research can provide insights to firms, retailers, and new entrepreneurs venturing into the smartphone business and formulation of marketing strategies.